The phonetics and phonology of laryngeal features in Native American languages - Avelino Becerra, Heriberto, 1968-; Coler, Matt; Wetzels, Leo (Brill's studies in the indigenous languages of the Americas ;, 2016)
"This book presents unique insights into laryngeal features, one of the most intriguing topics of contemporary phonetics and phonology. It investigates in detail properties such as tone, non-modal phonation, non-pulmonic production mechanisms (as in ejectives or implosives), stress, and prosody. What makes American Indigenous languages special is that many of these properties co-exist in the phonologies of languages spoken on the continent. Taking diverse theoretical perspectives, the contributions span a range of American languages, illustrating how the phonetics and phonology of laryngeal features provides insight into how potential articulatory and aero-acoustic conflicts are resolved, which contrastive laryngeal features can co-occur in a given language, which features pattern together in phonological processes and how they evolve over time. This contribution provides the most recent research on laryngeal features with an array of studies to expand and enrich the fascinating field of phonetics and phonology of the languages of the Americas. Contributors include Heriberto Avelino, Thiago Chacon, Didier Demolin, Jose Elias-Ulloa, Melissa Frazier, Matthew Gordon, Sharon Hargus, Larry M. Hyman, Keren Rice, Wilson De Lima Silva, Luciana Storto, and Siri G. Tuttle."--